2020
DOI: 10.1021/acsnano.0c07426
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Imaging of Ferroelastic Domain Dynamics in CsPbBr3 Perovskite Nanowires by Nanofocused Scanning X-ray Diffraction

Abstract: The interest in metal halide perovskites has grown as impressive results have been shown in solar cells, light emitting devices, and scintillators, but this class of materials have a complex crystal structure that is only partially understood. In particular, the dynamics of the nanoscale ferroelastic domains in metal halide perovskites remains difficult to study. An ideal in situ imaging method for ferroelastic domains requires a challenging combination of high spatial resolution and long penetration depth. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 62 publications
3
20
0
Order By: Relevance
“…These results are compatible with the recent nano‐scale X‐ray diffraction imaging results which found that the domains formed at 350 K are partially stable subject to cycling to lower and higher temperatures. [ 38 ]…”
Section: Figurementioning
confidence: 99%
“…These results are compatible with the recent nano‐scale X‐ray diffraction imaging results which found that the domains formed at 350 K are partially stable subject to cycling to lower and higher temperatures. [ 38 ]…”
Section: Figurementioning
confidence: 99%
“…The instrument provides enough space for hosting compact sample environments, which contributes to its versatility. This endstation has been in user operation since summer 2017 and has produced impactful results in different fields of physics Nukala et al, 2021;Neckel et al, 2022), material science (Bjo ¨rling et al, 2020a;Dzhigaev et al, 2020Dzhigaev et al, , 2021Hammarberg et al, 2020;Ji et al, 2020;Marc ¸al et al, 2020Marc ¸al et al, , 2021Reimers et al, 2022;Li et al, 2022b) and biology (Silva Barreto et al, 2020;Gustavsson et al, 2021), using scanning and local approaches while exploiting scattering, fluorescence and coherent X-ray methods. It has also received considerable interest from communities of soft-matter physics (Nissila ¨et al, 2021;Huss-Hansen et al, 2022) and geology (Warlo et al, 2022) and has recently produced the first results of 3D ptychography in Bragg, demonstrating the great opportunities provided to crystal microscopy by the high coherent flux of fourth-generation sources (Li et al, 2022a).…”
Section: Introductionmentioning
confidence: 99%
“…The main categories of methods regularly used are CDI in forward and Bragg geometries, nano-diffraction in both geometries, and 2D XRF and X-ray absorption near-edge structure spectroscopy (XANES) imaging. Examples of experiments performed are diffraction and strain mapping of nano-wires (Chayanun et al, 2019;Hammarberg et al, 2020;Dzhigaev et al, 2020;Marçal et al, 2020); single nano-particle coherent Bragg imaging (Bjö rling et al, 2019(Bjö rling et al, , 2020bDzhigaev et al, 2021); extreme pressure nano-diffraction (Ji et al, 2020); ptychographic tomography (Kahnt et al, 2020); 2D XRF imaging of plant, animal and human cells (Silva Barreto et al, 2020); nano-diffraction (Nissilä et al, 2021); and X-ray technology development (Akan et al, 2020;Chayanun et al, 2020). The tomography endstation, based on Fresnel zone plate (FZP) optics, is currently under development.…”
Section: Introductionmentioning
confidence: 99%